Investigation of Salt-Frost Heaving Rules and Mechanical Properties of Chlorite Saline Soil along the Duku Highway under Freezing-Thawing Action - Xuebang Huang; Zizhao Zhang; Zezhou Guo; Ruihua Hao; Qianli Lv; Tianchao Liu; Tiansheng Zhou (Advances in Civil Engineering)
Aiming to investigate salt-frost heaving rules and the mechanical properties of natural saline soil along the Duku Highway subjected to multiple freezing-thawing cycles, we collected natural saline soil samples from the alluvial-proluvial plain in front of the Dushanzi Mountain at the starting point of the Duku Highway. Then, we conducted mineral composition analysis tests, essential laboratory physical property measurement, large scale multiple freezing-thawing cyclic salt-frost heaving tests, shear strength tests, and unconfined compressive strength tests on the samples. According to the test results presented, the collected saline soil differed from saline soil in other regions and fell into “chlorite saline soils.” As the number of freezing-thawing cycles increased, the overall salt-frost heaving capacity increased and then decreased in the freezing process but first reduced and then increased in the thawing process. Thus, the salt-frost heaving capacity was cumulative in freezing/thawing cycles. The peak salt-frost heaving capacity reached a maximum after 1 freezing-thawing cycle and then dropped drastically and fluctuated regularly. After 6 freezing-thawing cycles, the displacement deformation and time formed a new equilibrium. After 7 freezing-thawing cycles, the displacement and deformation of the soil no longer appear negative. As the number of freezing-thawing cycles increased, the cohesive force of saline soil first increased and then dropped steadily, the internal friction angle first dropped and then increased steadily, and the unconfined shear strength first increased and then decreased. These research results provided data supporting the prevention and controlling highway saline soil disasters with insightful references for the other projects in this region.